The clinical characteristics and genotype analysis of LAMB2 gene mutation - Li, Guangbo; Su, Dequan; Liu, Cuihua; Cao, Guanghai; Zhan, Zhuqin; Liao, Jianying (Frontiers in Medicine, 2024)
Purpose To report a case of steroid-resistant nephrotic syndrome caused by a LAMB2 gene mutation, examine the associated literature, outline the clinical and genetic features of Pierson syndrome, and deepen the clinical comprehension of this condition. Method The study involved retrospective summary and analysis of the clinical presentations, genetic mutation features, and prognosis of one case involving a LAMB2 gene mutation. PubMed, Medline, Web of Science, CNKI, and Wanfang databases were searched to gather and summarize information on the pathological phenotypes and genotypic alterations associated with LAMB2 mutations. Result A 9-month-old infant presented with edema and massive proteinuria, along with horizontal nystagmus and miosis, manifesting clinically as steroid-resistant nephrotic syndrome. Ocular symptoms prompted both a kidney biopsy and genetic testing. The biopsy revealed minimal change disease, while genetic testing identified compound heterozygous mutations in the LAMB2 gene: c.1405C > T (p.R469X) and c.1066 T > A (p.C356S), inherited from the father and mother, respectively. These mutations were determined to be novel. The diagnosis was confirmed as a LAMB2 gene mutation. A literature review of 26 cases with LAMB2 mutations indicated these typically presented as steroid-resistant or congenital nephrotic syndrome, with 14 cases also displaying ocular symptoms. Among the 18 cases undergoing kidney biopsy, findings included focal segmental glomerulosclerosis in 10 cases, minimal change disease in 4 cases, diffuse mesangial sclerosis in 2 cases, IgM nephropathy in 1 case, and mesangial proliferation in 1 case. Electron microscopy in 10 cases showed basement membrane splitting. Genetic analysis revealed 15 cases with compound heterozygous mutations, 5 with homozygous mutations, 3 with heterozygous mutations, 2 with frame-shift mutations, and 1 with a truncating mutation. 16 out of the 26 reported cases progressed to end-stage kidney disease. Conclusion Mutations in the LAMB2 gene primarily manifest as steroid-resistant or congenital nephrotic syndrome, often accompanied by ocular abnormalities, suggesting a strong likelihood of this disease. The results of genetic testing offer a foundational basis for clinical diagnosis. The identification of a new mutation site in this case expands the known spectrum of mutations in the LAMB2 gene. Unfortunately, the prognosis associated with this condition is generally poor.